GAMBARAN KEJENUHAN BELAJAR SISWA SMK KELAS X - Siti Rosmaidah; Ecep Supriatna; Rima Irmayanti (IKIP Siliwangi, 2021)
The saturation of learning has a big impact on the decrease in learning motivation of learners. Students who initially do not know the symptoms of learning saturation may consider the learner to be lazy to learn. But the saturation of learning that students experience can result in decreased test scores and assignments, not following the KBM process, can even ditch the school because it feels lazy. This study uses a qualitative approach. The data collection conducted are interviews and observations. The results of the study indicate that the sense of boredom in learning experienced by students is that they lack support from themselves, outside themselves and in a bad environment, thus making them lazy to take part in learning. Keywords: saturation of learning, students